Variabilidade espaço-sazonal de atributos químicos físicos e biológicos em topossequência no Cariri Paraibano - Alves, Marco Aurélio Barbosa (2019)
Soil-related natural resources in dryland environments, such as the Caatinga, have suffered from deterioration impacts due to the absence of conservation practices coupled with inadequate soil use, without taking into account the spatiotemporal variability of attributes that are variable as a function of time and space. The objective of this study was to evaluate the spatial-seasonal variability of physical, chemical and biological attributes in a toposequence of Carossian Neosols of Paraíba. The geostatistics allied to kriging can identify and map specific management zones by mathematical models capable of showing the degree of spatial dependence and interpolation of data with no trend in non-sampled points for confection of isoline maps. Soil collections at different times of the year taking into account the seasonality of the rains (dry period and rainy season) can be an effective methodology in determining the seasonal variability of the attributes. For studies of diversity of edaphic organismos the determination of ecological indices such as: Wealth, Shannon, Simpson and Pielou. The study was carried out in a compartmentalized toposequence in three positions: shoulder, middle third and lower third, in the Private Reserve of Natural Patrimony (RPPN), Fazenda Almas, in Cariri da Paraibano. Soil attributes presented spatiotemporal variability in the positions of Shoulder, Middle and Lower Thirds. The CO2 flux was influenced only by soil moisture, since the soil temperature was constant with the seasonal rainfall. The Neosols of Cariri Paraibano show a high diversity of edaphic macroarthropods that have their composition of the community influenced directly by the relief positions.